(untitled) (Dhaka University Journal of Linguistics, 2011)
This paper attempts to describe the word formation process known as ’conversion’ and a specific lexeme impact which is converted from noun to verb basically by American native speakers or news reports. But many people think that this process is to nouns and exploit them as verbs and many of such usages as impact are really disdainful. My purpose is to provide actual examples of impact taken from American newspapers and give reasons behind the functional shift of impact. As newspapers use the most standard language of time, this paper tries to show how the verb impact has established its transitive use in American Standard English, having gained more semantically emphatic force than its synonymous verb effect. Key words: word formation; American Standard English; news paper DOI: 10.3329/dujl.v2i4.6905 Dhaka University Journal of Linguistics Vol.2(4) August 2009 pp.161-172